Endoscopic transpterygoidal repair of a large cranial defect with cerebrospinal fluid leak in a patient with extensive osteoradionecrosis of the skull base: case report and technical note - Brand, Y.; Lim, E.; Waran, V.; Prepageran, Narayanan (Cambridge University Press, 2015)
Background: Endoscopic endonasal techniques have recently become the method of choice in dealing with cerebrospinal fluid leak involving the anterior cranial fossa. However, most surgeons prefer an intracranial approach when leaks involve the middle cranial fossa. This case report illustrates the possibilities of using endoscopic techniques for cerebrospinal fluid leaks involving the middle fossa. Case report: A 37-year-old male patient presented with multiple areas of cranial defect with cerebrospinal fluid leak due to osteoradionecrosis following radiation for nasopharyngeal carcinoma 4 years earlier. Clinical examination showed involvement of all cranial nerves except the IInd and XIth nerves on the left side. A prior attempt to repair the cerebrospinal fluid leak with craniotomy was not successful. Conclusion: This case demonstrates the successful endoscopic repair of a large cranial defect with cerebrospinal fluid leak.